The dowel technique for first metatarso-phalangeal joint arthrodesis in revision surgery with bone loss. Issue 3 (June 2018) - Malagelada, Francesc; Welck, Matthew J.; Clark, Callum
Highlights: Our case series presents a novel technique for arthrodesis of the first MTPJ in the presence of bone loss. Its advantages include its versatility, the potential for restoration of hallux length/alignment and ease of fixation. A fusion rate of 100% was achieved at a mean of 9.3 weeks in our series of 8 patients, without major complications. In all cases the HVA improved postoperatively and the length of hallux also increased consistently. This was especially seen in those cases which were revised from a non-arthroplasty index surgery (arthrodesis, Keller). Abstract: Background: The operative management of failed first metatarso-phalangeal joint (MTPJ) surgery is often complicated by bone loss and shortening of the hallux. Restoration of first ray length and alignment often cannot be achieved with in situ fusion and reconstruction techniques with bone graft are therefore required. We present a novel technique of longitudinal (proximo-distal) bone dowel arthrodesis for first MTPJ arthrodesis with bone loss. Methods: Between August 2007 and February 2015, eight patients have been treated by the senior author with this technique. The mean age at surgery was 60.5 years (range 45–80) with seven females and one male. Index surgery was MTPJ arthrodesis (three patients), Keller excision arthroplasty (two patients), MTPJ hemiarthroplasty (two patients) and silastic arthroplasty (one patient). Clinical and radiological fusion was assessed and other radiological measurements included hallux valgus angle (HVA) and length of the hallux (LOH). Results: All patients achieved fusion at a mean of 9.3 weeks (range 6–12) from surgery and only one patient required removal of metalwork. There were no major complications. The HVA improved in all cases from 21.4 ± 2.8 pre-operatively to 11.6 ± 3.5 post-operatively (p > 0.05). The LOH also increased in all cases from 82.1 ± 8.3 mm to 86.7 ± 8.2 mm (p > 0.05). The subgroup of patients who were revised from an arthroplasty, where maintenance of length rather than increase in length was desirable (hemiarthroplasty, silastic) had significantly lower increase in LOH than those revised from a non-arthroplasty index surgery (arthrodesis, Keller) (p = 0.029). Conclusion: The dowel technique is successful for first MTPJ arthrodesis revision surgery with optimal union rates and satisfactory radiographic and clinical outcomes. It is an effective and versatile option for managing bone loss and deformity of the hallux.